(untitled) - Fall , Matar (2009)
Reforming Urban Water Utilities in Western and Central Africa: Experiences with Public-Private Partnerships - Volume 1: Impact and Lessons Learned. Matar Fall, Philippe Marin, Alain Locussol, Richard Verspyck. The Western and Central Africa has one of the longest experiences with public-private partnerships (PPPs) in the developing world, both for water supply and for combined power and water supply utilities. Cote d'Ivoire has a successful partnership dating from 1959, and over the last two decades as many as 15 countries (out of 23 in the region) have experimented with PPPs: eight for water supply operations alone and seven for combined power and water supply operations. This discussion paper documents the region's experience with PPPs for urban water supply in a comprehensive manner to help inform the current debate about the benefits brought by PPPs, in the context of helping Africa to achieve the Millennium Development Goals (MDG). Eleven PPPs have been studied, and detailed performance indicators
Keywords: Water supply,Cung cấp nước